Comparison of Working Length Determination in Mandibular Single-Rooted Teeth - Ruqayya Sana; Farzana Rehman; Shabana Rehman; Rashid Javaid (Gandhara University, 2021)
OBJECTIVES: The objective of this study was to compare working length calculated with conventional radiographs and an electronic apex locator (IPEX II) during the root canal treatment of mandibular anterior teeth. METHODOLOGY: A cross-sectional study was done in the Department of Operative Dentistry, Sardar Begum Dental Hospital, Peshawar during February and March 2018. A consecutive sampling technique was used for sampling. Only 30 patients fulfilled the inclusion criteria of our study. Detailed medical and dental history was taken. Only patient fulfilling inclusion criteria were enrolled in the study. Data were analyzed using SPSS version 20. RESULTS: The mean age for patients was 45.33±5.16. 33% out of 30 patients (10) were male and 20 were females. The mean working length calculated from radiographs was 22.25±1.29 (min 20.09-max 24.10). The mean working length calculated by the electronic apex locator (IPEX II) was 22.17±1.28 (min 20.00-max 24.07). The mean difference between working length calculated by radiograph and electronic apex locator was -0.084mm, which means the working length determined by radiographs and by electronic apex locator has no difference in mandibular anterior teeth with single canals. CONCLUSION: Both the methods can be used effectively in endodontics for single-rooted mandibular teeth, but if both are used in combinations can lead to an improvement in the working length accuracy, which may significantly reduce the number of radiographs exposure, and increase the success and comfort for endodontic patients. KEYWORDS: Working Length, Apex Locator, Conventional Radiograph